German experience in the management of ELGAN infants - Fuchs, Hans (Acta Biomedica Atenei Parmensis, 2015)
Of 680 000 infants born in Germany a year roughly 10% are preterm and 1% are very preterm. They are treated in around 150 level 1 perinatal centers and there are various credos how to best treat the ELGAN infant. However, many centers include the use of a sustained inflation for lung aeration in the standard protocol of delivery room care in Germany. As a result of the large studies on delivery room care, a trend for earlier or prophylactic surfactant in the most immature infants can be observed, however, surfactant is increasingly given in a new less invasive way called LISA. German randomized controlled trials on LISA , on permissive hypercapnia in the premature infants and a German initiated European trial on inhaled steroids have been completed and preliminary results are available. NIRS so far mostly is used for research reasons; however, the number of centers that monitor brain oxygenation for clinical reasons to guide hemodynamic management is increasing. A recent initiative was able to tremendously reduce the rate of IVH by prospective multidisciplinary surveillance.